Pengaruh Variabel Makroekonomi Terhadap Profitabilitas Perbankan Syariah di Indonesia Periode 2010-2013 - Tinton Saputra, Anas, Drs. Yuni Prihadi Utomo, MM, M. Muhtarom, SH., MH (2015)
This study investigates the impact of macroecnomic variables on islamic banking profitability in Indonesia for the period 2010 to 2013 which is proxied by Return On Assets (ROA). The variables of macroeconomic in this study include inflation, BI Rate, Gross Domestic Product, money supply, and exchange rate. The sampling selection method is used in this study is convience sampling and obtained 6 Islamic bank which meet the criteria, those are Bank Muamalat Indonesia, Bank Syariah Mandiri, BRI Syariah, Bank Mega Syariah, Bank Bukopin Syariah, and BCA Syariah. This study uses Pooled Ordinary Least Square (POLS) or panel data as a tool analysis. The results show that BI Rate has a negative effect and significant on Return On Assets of Islamic bank. Exchange rate has a positive effect and significant on Return On Assets of Islamic bank. Whereas inflation, Gross Domestic Product, and money supply have no signficant effect on Retun on Assets of Islamic bank.